2006
DOI: 10.1371/journal.pbio.0040066
|View full text |Cite
|
Sign up to set email alerts
|

Removing the Threat of Diclofenac to Critically Endangered Asian Vultures

Abstract: Veterinary use of the nonsteroidal anti-inflammatory (NSAID) drug diclofenac in South Asia has resulted in the collapse of populations of three vulture species of the genusGyps to the most severe category of global extinction risk. Vultures are exposed to diclofenac when scavenging on livestock treated with the drug shortly before death. Diclofenac causes kidney damage, increased serum uric acid concentrations, visceral gout, and death. Concern about this issue led the Indian Government to announce its intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
146
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(150 citation statements)
references
References 17 publications
3
146
0
1
Order By: Relevance
“…Diclofenac and meloxicam concentrations in extracts were determined by liquid chromatography with electrospray ionization mass spectrometry (LC-ESI/MS). The limit of quantification (LOQ), back-calculated to concentration in wet tissue, was 0.01 mg kg 21 . Detailed protocols for extraction and analysis of these NSAIDs were reported previously [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Diclofenac and meloxicam concentrations in extracts were determined by liquid chromatography with electrospray ionization mass spectrometry (LC-ESI/MS). The limit of quantification (LOQ), back-calculated to concentration in wet tissue, was 0.01 mg kg 21 . Detailed protocols for extraction and analysis of these NSAIDs were reported previously [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is theoretically possible using captive vultures, there are a large number of NSAIDs available, many of which may also be administered in combinations. Because most vulture species, including Gyps spp., are now regionally or globally endangered (IUCN, 2010), in vivo trials on all drugs or combinations are not feasible, especially given the large sample sizes required to prove drugs to be safe (as was the case for meloxicam; Swan et al, 2006a). One alternative would be to use a bird species that is common, widely distributed, easy to handle, and not endangered.…”
Section: Introductionmentioning
confidence: 99%
“…However, once conclusively implicated in the extensive vulture mortality, measures were taken (in 2006) to withdraw it from use within the veterinary sector and to identify an effective replacement that would not harm vultures. Rigorous safety trials identified meloxicam as a suitable alternative [92,93] and a campaign was then mounted to work with government authorities and pharmaceutical manufacturers. Banned (in India, Nepal and Pakistan) for veterinary use since 2006, the perception of diclofenac's efficacy nonetheless persists.…”
Section: The Situation On the Asian Subcontinentmentioning
confidence: 99%